Pengaruh Tingkat Inflasi, Nilai Tukar Rupiah, Jumlah Uang Beredar dan Produk Domestik Bruto terhadap Indeks Harga Saham Gabungan di Bursa Efek Indonesia - Fujiono Fujiono; Rusdi Hidayat Nugroho (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
In carrying out a life cycle, we need to make an investment so that the funds we currently have can be used for the next few years. This study aims to determine the simultaneous and partial influence of inflation, interest rates, rupiah exchange rate, the money supply and gross domestic product on the composite stock price index. The sampel in this study amounted to 40 data with quarterly data that was limited to the 2011:Q3 to 2021:Q2 observation period and was obtanied through complete sampling. The data was analyzed using multiple linear regression analysis techniques. Hypothesis tested using F test and t test. The results showed that simultaneously (Test F) variable inflation, interest rates, rupiah exchange rate, the money supply and gross domestic product have a positive and significant effect on the composite stock price index (IHSG). Partially (Test t) rupiah exchange rate have a positive and significant effect on the composite stock price index (IHSG). the money supply have a have a positive and no significant effect on the composite stock price index (IHSG). Mean while inflation and gross domestic product have a negatif and no significant effect on the composite stock price index (IHSG). Keywords: Inflation, Rupiah Exchange Rate, The Money Supply, Gross Domestic Product Composite Stock Price Index